2014
DOI: 10.1039/c4ce01595a
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel method to grow mono-/few-layered MoS2films and MoS2–graphene hybrid films for supercapacitor applications

Abstract: The controlled synthesis of highly crystalline MoS 2 atomic layers remains a challenge for practical applications of this emerging material. We demonstrate a facile method to synthesize crystalline mono-layer / few-layered MoS 2 thin films at liquid-liquid interface which can be suitably transferred on substrates. The films are characterized for its crystal structure by XRD and for the morphology by SEM and TEM. MoS 2 nanosheet-graphene nanosheet (MoS 2 -GNS) hybrid films have been developed by the application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
73
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(78 citation statements)
references
References 73 publications
(132 reference statements)
4
73
0
1
Order By: Relevance
“…[204][205][206][207][208][209][210][211][212] The common transition metal sulfi des used as pseudocapacitive electrodes are MoS 2 , WS 2 VS 2 and NiCo 2 S 4 . [213][214][215][216][217][218] Furthermore, transition metal sulfi des can also be added into nanocarbon architectures to serve as fl exible SC electrodes. [ 214,219 ] Because different transition metal oxides/ hydroxides have been successfully prepared in the graphene/CNTs composite architectures, asymmetric SCs can be obtained using these composite architectures as electrodes.…”
Section: Graphene/cnt/transition Metal Oxide Composite Architecturesmentioning
confidence: 99%
See 1 more Smart Citation
“…[204][205][206][207][208][209][210][211][212] The common transition metal sulfi des used as pseudocapacitive electrodes are MoS 2 , WS 2 VS 2 and NiCo 2 S 4 . [213][214][215][216][217][218] Furthermore, transition metal sulfi des can also be added into nanocarbon architectures to serve as fl exible SC electrodes. [ 214,219 ] Because different transition metal oxides/ hydroxides have been successfully prepared in the graphene/CNTs composite architectures, asymmetric SCs can be obtained using these composite architectures as electrodes.…”
Section: Graphene/cnt/transition Metal Oxide Composite Architecturesmentioning
confidence: 99%
“…[213][214][215][216][217][218] Furthermore, transition metal sulfi des can also be added into nanocarbon architectures to serve as fl exible SC electrodes. [ 214,219 ] Because different transition metal oxides/ hydroxides have been successfully prepared in the graphene/CNTs composite architectures, asymmetric SCs can be obtained using these composite architectures as electrodes. [220][221][222][223][224][225] For example, the asymmetric SCs assembled by rGO/CNT/MnO 2 and rGO/ CNT/PPy hybrid fi lms are able to provide an output voltage of 1.6 V, and deliver high energy/power density (22.8 W h kg −1 at 860 W kg −1 and 2.7 kW kg −1 at 6.2 W h kg −1 ).…”
Section: Graphene/cnt/transition Metal Oxide Composite Architecturesmentioning
confidence: 99%
“…[16][17][18] Some of the TMCs like MoS 2 , SnS 2 , and WS 2 , have been studied extensively owing to their exceptional applicability in areas like electronics, 18-20 energy storage, [21][22][23][24] energy conversion, [25][26][27] optoelectronics etc. 39 Similarly WS 2 /RGO showed a specific capacitance of 350 F/g which is 5 times higher as compared to bare WS 2 . 30,31 They have been studied in their pristine form as well as hybrid form with graphene/reduced graphene oxide (RGO).…”
Section: Introductionmentioning
confidence: 95%
“…For examples, Leite and coworkers developed a microwave-assisted route to fabricate a hybrid of MoS 2 /reduced graphene oxide with the specific capacitance of 265 F g À1 at 10 mV s À1 [24]. Patil and coworkers reported that the MoS 2 /graphene hybrid film electrode possessed a specific capacitance of 282 F g À1 at a scan rate of 20 mV s À1 [25]. Therefore, rational combination of MoS 2 with graphene can be expected as an ideal way to fabricate the electrode materials with excellent specific capacitance.…”
Section: Introductionmentioning
confidence: 98%